PENERAPAN ALGORITMA RIVERT CODE 4 (RC 4) PADA APLIKASI KRIPTOGRAFI DOKUMEN - Redaksi Tim Jurnal (PETIR, 2018)
The development of information technology, has made the information as a basic requirement for everyone. To secure the information we have, one of the techniques of data and information security is cryptography. Therefore, the authors make an application that can maintain the confidentiality of the information and the intended application is web-based cryptographic applications. This application can be used to secure the data. In this application, the cryptographic algorithm to be used is the algorithm Rivest Code 4 (RC4). RC4 is a stream cipher algorithm that processes the type of data input unit. Algorithms Rivest Code 4 (RC4) is also part of a symmetric algorithm, in which the encryption and decryption process has the same key. Making these applications using the programming language PHP and MySQL. Modeling methods in making this application is a method of UML (Unified Modeling Language). The results to be achieved from this research is biased document cryptographic applications perform encryption and decryption algorithms Rivest document with Code 4 (RC4).